Return to play following craniotomy for non-traumatic brain lesions - Jovanna A. Tracz; Matthew L. Farmer; Mark Hughes; Debraj Mukherjee; Paul M. Brennan (World Neurosurgery: X)
Objective: Return to play (RTP) decisions after cranial surgery are important to patients. Most published data relate to RTP following sports-related brain injury. This study investigated factors that influence neurosurgical RTP decision-making following craniotomy for non-traumatic brain lesions. Methods: A patient scenario-based survey was distributed to U.S. and Europe-based neurosurgeons via the American Association of Neurological Surgeons/Congress of Neurological Surgeons Tumor Section and the European Association of Neuro-Oncology. From one core patient scenario, 5 further scenarios were developed involving patients of varying age, sport preference, tumor pathology, and craniotomy approach. Respondents provided RTP recommendations and factors important in forming these recommendations. Results: Forty-one responses were received; Europe (48%), U.S. (37%). The most commonly cited factors influencing RTP decision-making across scenarios were symptomatic recovery (85.4%), resolution of blood and/or air on imaging (43.4%), and patient demand (31.7%). The sports with the longest average RTP timeline were boxing (10.3 months), rugby (8.7 months), and American football (8.5 months) in the core patient scenario. Twenty-nine percent of neurosurgeons requested neuroimaging before determining RTP recommendations in this scenario, more commonly in America than Europe (46.7% and 5.0% respectively, p = .006). Conclusions: Although limited by sample size, the data provides a foundation to support development of a systematic approach to RTP decision-making following craniotomy for brain lesions of non-traumatic etiology. Future work to develop consensus guidelines will benefit from objective data about outcomes, particularly in relation to repeat imaging prior to RTP.